Control of Dengue Hemorrhagic Fever through Community Networking and Abstaining from the Use of Mosquito Larvicide, Linfa Sub-district, Yangchumnoi District, Sisaket Province - Suebla, Phiangphen (Journal of Health Science of Thailand, 2017)
Dengue hemorrhagic fever (DHF) is a health problem in Si Sa Ket Province. Prevention efforts have been put in plane in all communities. However, with the use of massive chemical agents to control mosquito breeding sites, community participation has been limited. Health officials were unable to get access to all areas to implement prevention and control strategies. Therefore, Linfa Sub-district has modifies the control strategy by the use of multi-sectoral networking to handle to problem. The objective of this study was to assess the effectiveness of an approach to promote involvement of various sectors to counter the epidemic without using chemicals. This action research covered all 14 villages of the sub-district with the involvement of 389 community leaders during the period from October 2012 to June 2013. The study tools included surveillance data in the sub-district, village health volunteers’ personal records, and records for household survey for mosquito larva indexes. The study was conducted in 2 phases beginning with the preparation phase in which a mapping was made, and stakeholder meeting was organized with the participation of the president and the members of sub-district administration organizations, village heads and assistants, family leaders from every household, and school representatives altogether 389 people with the aim to make them aware of the DHF problem and make an agreement for community participation in the control. The second phase was the operation period in which implementation strategies were conducted including public relation to motivate villagers to take care of their house, elimination of mosquito larva, carrying out random larva survey by village health volunteers from other villages, sharing survey data and improving the work. As a result, household larva indexes decreased and there was no case of DHF in the sub-district. There was no purchase of chemicals in the campaign. This approach should be promoted for the strengthening of DHF prevention on a routine basis regardless of the presence of the epidemic.